2020
DOI: 10.1002/hbm.25043
|View full text |Cite
|
Sign up to set email alerts
|

Numerical working memory alters alpha‐beta oscillations and connectivity in the parietal cortices

Abstract: Although the neural bases of numerical processing and memory have been extensively studied, much remains to be elucidated concerning the spectral and temporal dynamics surrounding these important cognitive processes. To further this understanding, we employed a novel numerical working memory paradigm in 28 young, healthy adults who underwent magnetoencephalography (MEG). The resulting data were examined in the time‐frequency domain prior to image reconstruction using a beamformer. Whole‐brain, spectrally‐const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…By observing stroke patients before and after the rehabilitation, a specific brain recovery pattern emerged, characterized by a widespread increased FC in the beta in the post-condition. The functioning of the beta frequency band has previously been related, in healthy population, to different cognitive tasks such as working memory (67)(68)(69), attention (70), and motor performance (71). On the contrary, our neurophysiological data were acquired during resting state (RS) which has been shown that is the most stable condition across patients with different symptomatology and it also has been considered a hallmark for clinical diagnosis and monitoring the recovery of patients that underwent a rehabilitation, both in MRI (18,72) and MEG studies (22,73).…”
Section: Discussionmentioning
confidence: 99%
“…By observing stroke patients before and after the rehabilitation, a specific brain recovery pattern emerged, characterized by a widespread increased FC in the beta in the post-condition. The functioning of the beta frequency band has previously been related, in healthy population, to different cognitive tasks such as working memory (67)(68)(69), attention (70), and motor performance (71). On the contrary, our neurophysiological data were acquired during resting state (RS) which has been shown that is the most stable condition across patients with different symptomatology and it also has been considered a hallmark for clinical diagnosis and monitoring the recovery of patients that underwent a rehabilitation, both in MRI (18,72) and MEG studies (22,73).…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting certain processes, neural resources can be redirected to processing relevant inputs for achieving the goal-directed behavior at hand. However, changes in alpha power have also been noted in instances of high cognitive demand, suggesting that increases in alpha power may be indicative of cognitive load and mental effort ( Koshy et al, 2020 ; Meyer et al, 2013 ; Rosen and Reiner, 2017 ). Gamma activity in frontoparietal regions has been less well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in amplitude that are not time-locked (i.e., TSA) to an event have been ascribed to different cognitive processes that can occur during maintenance. Namely, this pattern of ERD has been associated with manipulation of information held during the delay period (Koshy et al, 2020) as well as the use of cognitive control (Wei & Zhou, 2020). Klimesch et al (2007) suggested that ERD largely reflects both the anticipation of an upcoming response as well as attentional processes.…”
Section: Discussionmentioning
confidence: 97%
“…Event-related desynchronization has also been found in the alpha band during maintenance (Koshy et al, 2020). Decreases in amplitude that are not time-locked (i.e., TSA) to an event have been ascribed to different cognitive processes that can occur during maintenance.…”
Section: Discussionmentioning
confidence: 99%